PENGETAHUAN DAN SIKAP PASANGAN USIA SUBUR DALAM PENCEGAHAN HIV/AIDS - Rochany Septiyaningsih; Dhiah Dwi Kusumawati; Septiana Indratmoko (Poltekkes Kemenkes Medan, 2021)
Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) are still health problems faced by both developed and developing countries. One of the main factors that become obstacles is the stigma and discrimination against HIV sufferers in Indonesia which is still high. The age group most infected with HIV/AIDS in Indonesia is included in the population of couples of childbearing age. EFA is a couple (male and female) who are mature enough in all respects, especially their reproductive organs that are already functioning properly. At this time EFA must be able to maintain and utilize its reproduction properly. The purpose of this study is to describe the knowledge and attitudes of couples of childbearing age in preventing HIV/AIDS in the Work Area of ??the South Cilacap Health Center II. This study used a descriptive research design with a cross sectional approach. Samples were taken by random sampling technique, amounting to 30 respondents with univariate analysis. The results of this study were sufficient knowledge of respondents about HIV/AIDS 16 respondents (53.3%), both 12 respondents (40%) and less than 2 respondents (6.7%) as well as positive attitudes 24 respondents (80%) and negative attitudes 6 respondents (20%).